Удосконалення іміджу керівника закладу охорони здоров’я (на прикладі КНП Богодухівська ЦРЛ Богодухівської районної ради) - Фіранська, Валерія Євгеніївна (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Мета дослідження: теоретично обґрунтувати та розробити модель формування позитивного іміджу сучасного керівника закладу охорони здоров’я (на прикладі КНП Богодухівська ЦРЛ Богодухівської районної ради). Завдання дослідження: 1. Визначити теоретико-методичні аспекти формування іміджу керівника організації. 2. Проаналізувати процес формування іміджу сучасного керівника закладу охорони здоров’я (на прикладі КНП Богодухівська ЦРЛ Богодухівської районної ради). 3. Теоретично обґрунтувати та розробити модель формування позитивного іміджу сучасного керівника закладу охорони здоров’я (на прикладі КНП Богодухівська ЦРЛ Богодухівської районної ради).

Subject of research: the formation of a positive image of the modern head of the health care institution (on the example of the Bohodukhiv Central Regional Hospital of the Bohodukhiv District Council). The purpose of the research: to theoretically substantiate and develop a model for the formation of a positive image of the modern head of the health care institution (for example, the Bohodukhiv Central Regional Hospital of the Bohodukhiv District Council). Objectives of the study: 1. To determine the theoretical and methodological aspects of forming the image of the head of the organization. 2. To analyze the process of forming the image of the modern head of the health care institution (on the example of the Bohodukhiv Central Regional Hospital of the Bohodukhiv District Council). 3. Theoretically substantiate and develop a model for the formation of a positive image of the current head of the health care institution (on the example of the Bohodukhiv Central Regional Hospital of the Bohodukhiv District Council).
Improving the image of the head of a health care institution (on the example of Bohodukhiv Central Regional Hospital of the Bohodukhiv District Council)
Керівник роботи: Лазарєв Микола Іванович, доктор педагогічних наук, професор кафедри педагогіки, методики та менеджменту освіти Навчально-наукового-інституту “Українська інженерно-педагогічна академія”
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; заклад охорони здоров’я; керівник; комплексно-цільова програма; health care institution; head; complex-purpose program